2001
DOI: 10.1177/0146167201271005
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Sexism and Discrimination: The Importance of Respect for Men and Women

Abstract: Three studies supported the proposal that one important aspect of contemporary sexism is greater respect for men than for women and that this differential respect has a unique role to play in mediating hiring discrimination, distinct from gender stereotypes. In Studies 1 and 2, participants in a hiring paradigm evidenced bias favoring men on both respect ratings and hiring recommendations. Moreover, higher respect for male than for female applicants accounted for hiring discrimination. Some evidence that gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
(32 reference statements)
1
32
0
1
Order By: Relevance
“…In the realm of race relations, these concepts include aversive racism (Dovidio & Gaertner, 1998;Gaertner & Dovidio, 1986), symbolic racism (Sears, , 1998, and modern racism McConahay, 1986;McConahay & Hough, 1976). The gender bias literature refers to similar phenomena, such as modern sexism (Swim, Scott, Sechrist, Campbell, & Stangor, 1995), neosexism (Tougas et al, 1995), and contemporary sexism (Jackson, Esses, & Burris, 2001). Although each conceptualization of contemporary discrimination is slightly different, the mythologies behind the behaviors are well-represented by McConahay's depiction of modern racism against blacks:…”
Section: Contemporary Perspectives On Discriminationmentioning
confidence: 99%
“…In the realm of race relations, these concepts include aversive racism (Dovidio & Gaertner, 1998;Gaertner & Dovidio, 1986), symbolic racism (Sears, , 1998, and modern racism McConahay, 1986;McConahay & Hough, 1976). The gender bias literature refers to similar phenomena, such as modern sexism (Swim, Scott, Sechrist, Campbell, & Stangor, 1995), neosexism (Tougas et al, 1995), and contemporary sexism (Jackson, Esses, & Burris, 2001). Although each conceptualization of contemporary discrimination is slightly different, the mythologies behind the behaviors are well-represented by McConahay's depiction of modern racism against blacks:…”
Section: Contemporary Perspectives On Discriminationmentioning
confidence: 99%
“…Roberts (2004, pp.74-75) A number of researchers in psychology and sociology have indicated that respect is an important factor in building close interpersonal relationships (Frei & Shaver, 2002;Gottman, 1994Gottman, , 1996Hendrick & Hendrick, 2006;Zacchilli, Hendrick, & Hendrick, 2009). Respect is described as an attitude shaped by feelings and thoughts of quality of a person (Frei & Shaver, 2002;Jackson, Esses, & Burris, 2001). …”
Section: Brand Respectmentioning
confidence: 99%
“…Indeed, much research shows that men often resist affirmative action due to concerns about its effects on men (Beaton and Tougas 2001;Beaton et al 1996;Tougas et al 1995;Veilleux and Tougas 1989). On the other hand, other research shows that members of underprivileged groups sometimes absorb the ideologies promoted by members of dominant groups, including unflattering views about their own group (Jost and Banaji 1994;Jost et al 2001Jost et al , 2004 and higher respect for dominant groups (Jackson et al 2001). Thus, some women might tend to endorse affirmative action programs that are consistent with sexist assumptions and reject those that challenge them.…”
Section: The Present Researchmentioning
confidence: 99%